Developing a system dynamics model to study the impact of renewable energy in the short- and long-term energy security - Kirennesh Nair (KeAi Communications Co., Ltd., 2021)
This study discusses the impact that the share of renewable energy (RE) in the energy mix for total primary energy supply and electricity generation has on Malaysia's short and long-term energy security (ES). Three key dimensions of the ES of Malaysia have been studied thoroughly from the existing body of work to extract the indicators and their causal relation with each other. The system dynamics approach of modelling has been implemented to quantitatively analyse the impact on the relevant energy security indicators. The results are optimistic towards the increase in the share of RE to ensure both short and long-term ES through an increase in production to reserve ratio, decrease in energy dependency, and import in the long run. The energy policy structure needs to incline more towards diversification of energy sources to ensure that RE holds a major share in the energy mix as per the current energy policy objectives. This approach of modelling ES can be critical towards future policy design through consolidated data and evidence. This research aims to facilitate the nation's policymakers to dwell upon the need for separate ES policy drafts. The next stage of this research would involve the stakeholders to collect and validate the model.